IMPACT OF SGLT2 INHIBITOR ON CARDIAC REMODELLING IN PATIENTS WITH CHRONIC HEART FAILURE Kityan S.A. - Kityan S.A. (Research Focus International Scientific Journal, 2025)
SGLT2 inhibitor reduces the risk of heart failure (HF) in diabetics, and it has shown to improve the prognosis of patients with HF across all ranges of left ventricular ejection fraction (LVEF), by preventing HF decompensations and cardiovascular death[1]. This raises the question of what other mechanisms underlie these effects beyond sodium–glucose cotransporter 2 (SGLT2) inhibition. The effect of SGLT2 inhibitors on cardiac remodelling evaluated by imaging and related biomarkers remains uncertain, with scarcity of studies in HF patients and contradictory results mainly focused on patients with diabetes and reduced LVEF[2,3] Indeed, no data exist supporting a direct effect of SGLT2 inhibitor on cardiac geometry, function and biomarkers in presence of HF, irrespective of LVEF. Adverse myocardial remodelling affecting the left ventricle is a key factor in the progression of HF and current well-established HF phenotypes are based on LVEF. However, other relevant players have received less attention, such as the left atrium. Indeed, the left atrium plays a critical role in cardiac function, particularly in left ventricular (LV) filling during diastole. Additionally, atrial dysfunction can directly lead to pulmonary congestion. Left atrial (LA) remodelling occurs in HF irrespective of the degree of LV systolic dysfunction, and can be observed in the presence of preserved or reduced LVEF[4,5] The geometry of the left atrium is a predictor for the development of HF in high-risk patients,[5] and has been consistently linked to higher rates of hospitalization and death in patients with HF[6,7]. As a result, atrial disease has become an important concept that has been highlighted in the most recent guidelines for HF from the European Society of Cardiology (ESC)[8]. The aim of this study was to investigate the impact of SGLT2 inhibitor on cardiac remodelling parameters, specifically LA remodelling, in patients with HF regardless of their LVEF.